PENGARUH PENGEMBANGAN KARIR DAN KEPUASAN KERJA TERHADAP KINERJA DOSEN DI POLITEKNIK MANUFAKTUR NEGERI BANDUNG - Supriyadi Sadikin (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
This research focuses on performance of the lecturers Bandung Polytechnic for Manufacturing. Some of the essential factors are how well the career development and how satisfied the lecturers to their job performance. Based on the background, the problems of this research is to reveal the influence of the career development and job satisfaction to the lecturer's performance. This research is aimed to describe the variables of career development, job satisfaction, and its influence to lecturer's performance. This research uses theories from Gary Dessler (1998:45), Kruglanski dan Mayseless (1993 : 43) and Faustino Cardoso Gomes, (2001: 142). The research is using quantitative approach with survey method and path analysis. The objects of this research are the lecturers of Bandung Polytechnic for Manufacturing (POLMAN Bandung) which population is 80 taken from the list of Daftar Urut Kepangkatan (DUK). According the result, we can conclude that the variables of career development and job satisfaction give significant positive influence to the lecturer's performance both simultantly and partially. It is suggested that in improving the performance of its lecturer, the management should always be focus on career development and job satisfaction as factors to achieve its the goals.